2016
DOI: 10.7717/peerj.2570
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics ofPseudomonas syringaepathovartomatoreveals novel chemotaxis pathways associated with motility and plant pathogenicity

Abstract: The majority of bacterial foliar plant pathogens must invade the apoplast of host plants through points of ingress, such as stomata or wounds, to replicate to high population density and cause disease. How pathogens navigate plant surfaces to locate invasion sites remains poorly understood. Many bacteria use chemical-directed regulation of flagellar rotation, a process known as chemotaxis, to move towards favorable environmental conditions. Chemotactic sensing of the plant surface is a potential mechanism thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
12
0
3
Order By: Relevance
“…Swimming motility of P. syringae pv. tomato DC3000 wild type (WT) and indicated mutants with empty vector (EV), pJN105 (79), or ϩAlgU expression vector pEM53 (80). Each strain was inoculated on Kings B (KB) medium (77) with 0.3% agar and incubated at 28°C for 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…Swimming motility of P. syringae pv. tomato DC3000 wild type (WT) and indicated mutants with empty vector (EV), pJN105 (79), or ϩAlgU expression vector pEM53 (80). Each strain was inoculated on Kings B (KB) medium (77) with 0.3% agar and incubated at 28°C for 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…Many bacteria use flagella-driven motility to respond to changes in their chemical environment, a process known as chemotaxis (Berg and Brown, 1972;Wadhams and Armitage, 2004;Clarke et al, 2016). In P. aeruginosa, chemotaxis pathwayrelated genes play an important role in flagellar motility, T4 pili formation, and biofilm formation (Hickman et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In P. aeruginosa, chemotaxis pathwayrelated genes play an important role in flagellar motility, T4 pili formation, and biofilm formation (Hickman et al, 2005). In Pseudomonas savastanoi and PstDC3000, chemotaxis plays a role in virulence (Matas et al, 2012;Clarke et al, 2016) and the rsmA2/rsmA3 mutant of PstDC3000 showed significantly reduced motility (Ge et al, 2019). It is well established that CsrA binding of flhD inhibits RNase E-mediated cleavage and enhances its translation rate in E. coli (Wei et al, 2001;Yakhnin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Within this group of mutations, we identified two genes present in both DQS4 T and SmR1: cheY (DQS_RS02075 and HSERO_RS09745), which is related to chemotaxis, and ampD (DQS_RS17190 and HSERO_RS01880), which is involved in peptidoglycan degradation. Chemotaxis is directly involved in modulating the movement of the flagellum in response to attractants, helping bacterial orientation and active motion for survival toward favorable conditions (31)(32)(33). In addition, four other genes encoding transmembrane chemoreceptors, also known as methyl-accepting chemotaxis proteins (MCPs), were identified in H. seropedicae.…”
Section: Fig 1 Tnseq Representation and Determination (A)mentioning
confidence: 99%